The development of the bio plastics production technology from old oil palm trunk sap. - C Kanapathi Pillai, K Sudesh Kumar (Universiti Sains Malaysia, 2015)
Oil palm is a common agricultural product in Southeast Asia. Its source-the oil palm trees--have an economic life span of approximately 20-25 years, after which old trees are felled and the farms, replanted. Therefore, the discarded oil palm trunks are suddenly available in large quantities, providing readily-available alternative sources for new products such as bioplastic. The sap extracted from the trunks contain large amounts of glucose, and sucrose which can be fermented into bioplastic by PHA produce bacteria. The capability of PHA produce bacteria to metabolized sugars is restricted. Hence, the production of PHB made from sap is influenced. We will try to develop the technology to produce PHA efficiently from the sap by gene modification technology or isolate a microbe which produces PHA efficiently from the sap. Kelapa sawit merupakan sejenis produk agrikultur yang biasa di Asia Tenggara. Sumbernya pokok kelapa sawit-mempunyai jangka hayat produktif selama 20-25 tahun, dan pokok yang tua kemudiannya ditumbangkan dan ditanam semula dengan pokok baru. Oleh sebab itu, batang pokok kelapa sawit diperolehi dalam kuantiti yang besar, membekalkan sumber alternatif yang sedia ada untuk produk baru, contohnya bioplastik. Nira yang diekstrakkan daripada batang pokok tersebut mempunyai kandungan glukosa dan sukrosa yang tinggi dan boleh difermentasi kepada bioplastik oleh bakteria penghasil PHA. Kebolehan bakteria penghasil PHA untuk metabolisasikan gula adalah terhad. Oleh itu, penghasilan PHA dari nira akan terjejas. Kami cuba mengkaji teknologi untuk menghasilkan PHA dengan efisien dari nira dengan menggunakan teknologi modifikasi genetik atau pemencilan mikrob yang menghasilkan PHA secara efisien dari nira.